1997
DOI: 10.1023/b:appa.0000031790.30821.57
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Ixodiphagus hookeri, a tick parasitoid, on Ambl yomma variegatum (Acari: Ixodidae) in a field trial in Kenya

Abstract: In an experiment to investigate the effect of the tick parasitoid, Ixodiphagus hookeri, on tick numbers on cattle, 150000 parasitoids were released over a period of 1 year in a field where ten cattle infested with multiple tick species were kept. Amblyomma variegatum was reduced from 44 to two ticks per animal while Rhipicephalus appendiculatus increased over the time of parasitoid release. During the time of release 51% of the nymphs of A. variegatum collected from the animals were parasitized. The recovery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 4 publications
2
26
0
Order By: Relevance
“…Perhaps of equal importance, the theoretical results obtained against the blacklegged tick are in close agreement with the results obtained in a Þeld release experiment conducted by Mwangi et al (1997) in Africa against Amblyomma variegatum (F). Their experiment is the only effort that has been reported that has tested the feasibility of controlling tick populations by the parasitoid release technique.…”
Section: Current Tick Control Options and Probable Costssupporting
confidence: 83%
See 3 more Smart Citations
“…Perhaps of equal importance, the theoretical results obtained against the blacklegged tick are in close agreement with the results obtained in a Þeld release experiment conducted by Mwangi et al (1997) in Africa against Amblyomma variegatum (F). Their experiment is the only effort that has been reported that has tested the feasibility of controlling tick populations by the parasitoid release technique.…”
Section: Current Tick Control Options and Probable Costssupporting
confidence: 83%
“…In the experiment conducted by Mwangi et al (1997) the parasitoids had no effect on Rhipicephalus appendiculatus (Newmann) ticks on the experimental animals. This tick species, therefore, is probably not a suitable host for the parasitoid used in their experiment.…”
Section: Current Tick Control Options and Probable Costsmentioning
confidence: 90%
See 2 more Smart Citations
“…Wasp females insert their ovipositors inside the tick and lays eggs (Hu et al, 1998); subsequently, the larval stage of the wasp consumes the entire internal of the engorged tick, and the adult wasp emerges from the tick host 30-57 days following oviposition (Wood, 1911). This wasp was first described parasitizing Rhipicephalus sanguineus in TX, USA (Howard, 1908), as well as other species belonging to the genera Dermacentor (Wood, 1911), Amblyomma (Mwangi et al, 1997), Hyalomma (Cooley, 1930), Haemaphysalis (Doube and Heath, 1975) and Ixodes (Wood, 1911;Boucek and Verny, 1954;Costa-Lima, 1915). Given the wide geographical distribution of these wasps, it is possible that allopatric populations of I. hookeri belong to different taxa (Collatz et al, 2011) and are characterized by different biological behaviors.…”
Section: Introductionmentioning
confidence: 99%